Reactualizing Akidah Akhlaq Education through the Qur’anic Poetry of KH. M. Qoyyim Ya’qub - Asih Wilujeng (Journal Of Islamic Education And Pesantren, 2024)
This study aims to analyze the reactualization of Aqidah Akhlak education through the Qur’anic Poetry (Syair Qur’any) of KH. M. Qoyyim Ya’qub as a medium for value internalization in madrasah. The research employed a qualitative approach using content analysis, hermeneutic analysis, and pedagogical reconstruction, strengthened through triangulation of sources, including textual documents of the poetry, interviews, and classroom observations. The findings indicate that the Qur’anic Poetry contains an integrative structure of values encompassing faith (iman), morality (akhlak), and practice (amal) within a reflective and symbolic Qur’anic linguistic aesthetic framework. The values of creed, such as tawhid and eschatological awareness, serve as the foundation for shaping both personal and social morality, conveyed through metaphors and poetic expressions that touch the affective dimension. Empirically, the integration of the poetry into classroom instruction fosters a more dialogical and reflective learning atmosphere, enhances students’ emotional engagement, and strengthens value retention and internalization. Pedagogically, the reactualization is implemented through reflective literacy, curriculum integration, and creative expression models. The study concludes that the Qur’anic Poetry of KH. M. Qoyyim Ya’qub is not merely a religious literary heritage but also a transformative instrument in developing contextual, humanistic Aqidah Akhlak education oriented toward holistic character formation.